Self-Control of Adolescent in using Smartphone - Sari, Indah Permata; Ifdil, Ifdil; Sano, Afrizal; Yendi, Frischa Meivilona (Universitas Negeri Padang, 2020)
Self-control is the ability to rule out or change responses in a person, as well as eliminate unwanted problems and refrain from doing anything necessary for adolescent in using smartphones. Self-control of adolescent in using smartphones in this study is viewed from aspects of self-discipline, deliberate / non-impulsive, healthy habits, work ethic and reliability. This study aims to describe self-control of adolescents in using smartphone. This research is a descriptive analytic study, with a sample of 246 adolescents at SMAN 2 Padang obtained using propotional stratified random sampling technique. The study used a questionnaire instrument complied using a likert scale mode. The results of this study indicate that self-control of adolescent in using smartphones is generally appropriate in the high category. This needs to be corrected and improved in order to avoid the negative effects of using a smartphone.